First record of the insect order Mecoptera (Hexapoda) from Uruguay - Machado, Renato Jose Pires; Morelli, Enrique; Heleodoro, Raphael Aquino; Silva, Vitor Cezar Pacheco Da (Zootaxa, 2025)
We report the first record of the insect order Mecoptera from Uruguay. A total of 31 specimens of Bittacus brasiliensis Klug, 1836 (Bittacidae), from six different departments in the country were herein studied. It provided a better understand of the species, allowing us to firstly describe a sexual dimorphism related to the maxillary palp, and endorsed a discussion about a close related species from Argentina, B. zelichi Williner. This is by far the largest known series of B. brasiliensis, and represents the southernmost records of the species.